Extrapleural pneumonectomy: still indicated? - Domen, Andreas (Transl Lung Cancer Res, 2018)
The optimal treatment of malignant pleural mesothelioma (MPM) has not yet been established and is still under investigation. Surgery is one of the pillars in the multimodality approach with the purpose of removing as much as visible tumor as possible and to relieve symptoms. To date, two major surgical procedures are available for removal or debulking of MPM that is considered to be resectable: [extended (e)] pleurectomy/decortication (P/D) and extrapleural pneumonectomy (EPP). Historically, EPP was regarded as the only way to achieve a macroscopic complete resection. However, in the last years, there is a shift in literature towards (e)P/D as the preferred surgical procedure whenever possible as several retrospective studies and meta-analyses showed a similar or lower long-term survival and higher perioperative mortality and postoperative morbidity in patients who been treated with EPP. On the other hand, no randomized-controlled trials regarding surgical treatment with (e)P/D or EPP exist and therefore level A evidence favoring one surgical procedure is lacking. In this review we provide a nuanced and well-considered answer to the question whether EPP is still indicated in the surgical treatment of MPM.